Preparation method of high-voltage sodium ferrous sulfate positive electrode material
Patent Information
- Application Number
- CN202611090490.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-30
AI Technical Summary
但NFS正极材料在高电位下存在循环性能较差、导电性较差等问题,具体为:NFS正极材料晶格中因为有SO42-电负性极强的离子存在,导致其中晶格中Fe与O的连接方式为Fe-O-S-O-Fe的连接方式,晶格内部电子导电性较差
[0022]本发明的一种高耐压硫酸亚铁钠(NFS)正极材料制备方法,通过二甲基咪唑、二氧化硫脲、尿素中的-NH键易失H+离子特性,能与主材中的金属离子进行螯合配位,形成较稳定的配位键,使得氮原子与NFS材料形成强耦合效应,形成稳定的Fe-N-C键,有效提升材料的电导性,阻止Na、Fe混排,提升材料内部结构稳定。Fe-N-C键的形成和表面碳层的形成能降低材料表面SO42-引起的电负性,有效阻止电解液与电极表面发生的副反应,提升材料耐高压性。
Smart Images

Figure CN123002902A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery cathode material technology, specifically a method for preparing a high-pressure-resistant sodium ferrous sulfate cathode material. Background Technology
[0004] Sodium sulfate (Na2SO4) is one of the main materials for synthesizing sodium ferrous sulfate (NFS) cathode materials. The successful development and commercialization of NFS cathode materials can effectively realize the resource utilization of solid waste sodium sulfate, opening up the core link of "recycling-regeneration-utilization" and building a green battery circular economy. However, NFS cathode materials have problems such as poor cycle performance and poor conductivity at high potentials. Specifically, this is because the NFS cathode material lattice contains SO4. 2- The presence of highly electronegative ions results in Fe-O bonds in the crystal lattice being Fe-OSO-Fe, leading to poor electronic conductivity within the lattice. Furthermore, SO42-... 2- Its extremely high electronegativity causes it to adsorb polar small molecules in the electrolyte, leading to numerous side reactions on the electrode surface and resulting in poor cycling performance. Therefore, improving electronic conductivity and suppressing SO42- are crucial. 2- Electronegativity is beneficial for improving the electrochemical performance and cycle stability of materials. Therefore, developing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material is of great significance for the development of next-generation high-energy-density, low-cost sodium batteries. Summary of the Invention
[0005] (a) Technical problems to be solved
[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing a high-pressure-resistant sodium ferrous sulfate cathode material. This invention uses nitrogen-containing small molecules as an organic carbon source to modify the internal Fe-OSO-Fe bond chain structure, thereby improving the material's electronic conductivity. Furthermore, it utilizes the inherent charge properties of nitrogen and Fe... 2+ By forming stable chelate bonds, a uniform artificial CEI film can be effectively constructed while stabilizing the internal structure, thereby effectively improving the high-pressure resistance of the material.
[0007] (II) Technical Solution
[0008] A method for preparing a high-pressure-resistant sodium ferrous sulfate cathode material, the method comprising the following steps:
[0009] Step 1: Add sodium sulfate, ferrous sulfate, carbon nanotubes, deionized water and dispersant to a mixing tank for dispersion and dissolution, and then add an alcohol solution containing nitrogen small molecules to obtain NFS precursor slurry.
[0010] Step 2: Use a spray dryer to spray dry the mixed slurry to obtain the NFS cathode material precursor;
[0011] Step 3: Place the prepared NFS cathode material precursor into a graphite crucible, place the graphite crucible into a low-temperature atmosphere furnace, and sinter to obtain the sintered NFS cathode material.
[0012] Step 4: The prepared NFS cathode material is pulverized using an air jet mill and then sieved through a 300-mesh sieve to obtain a high-pressure-resistant sodium ferrous sulfate cathode material with uniform particle size distribution.
[0013] Preferably, in step one, the molar ratio of sodium sulfate to ferrous sulfate is 1.25:1.75; and the mass of carbon nanotubes is 1-5% of the total solid mass.
[0014] Preferably, in step one, the nitrogen-containing small molecule is one or more of dimethylimidazole, thiourea dioxide, and urea, and its mass is 2-10% of the total solid mass;
[0015] Nitrogen is an excellent electron carrier. In this invention, combining the electron-carrying and ionic charge-carrying properties of nitrogen, a high-temperature, high-energy co-assembly technique is used to couple small nitrogen-containing molecules in situ onto the interior and surface of the NFS cathode material lattice, effectively improving the electronic conductivity and cycle stability of the NFS cathode material. This invention employs water-soluble small nitrogen-containing molecules such as dimethylimidazole, thiourea dioxide, and urea as nitrogen sources, increasing conductivity while effectively stabilizing metal ions. This effectively solves the cycle stability problem of the NFS cathode material at high potentials, improves the energy density of the NFS cathode material at the cell level, effectively reduces the watt-hour cost of sodium batteries, and greatly promotes the widespread application of sodium batteries.
[0016] Preferably, in step one, the dispersant is one of citric acid, glucose, oxalic acid, polyethylene glycol, polyethylene oxide, and ammonium polyacrylate.
[0017] Preferably, in step two, when performing spray drying, the inlet air temperature is set to 230°C and the outlet air temperature is set to 110°C.
[0018] Preferably, in step three, the sintering atmosphere is nitrogen, the sintering temperature is 300-380℃, the heating rate is 2℃ / min, and the sintering holding time is 8-12h.
[0019] Preferably, in step four, when using an air jet mill for pulverization, the particle size is pulverized to d. 50 ≤8um.
[0020] Preferably, a high-pressure-resistant sodium ferrous sulfate cathode material is prepared by the method described in any one of claims 1-6.
[0021] (iii) Beneficial technical effects
[0022] This invention discloses a method for preparing a high-pressure resistant sodium ferrous sulfate (NFS) cathode material, which utilizes the easily lost H- bonds in dimethylimidazole, thiourea dioxide, and urea. + The ionic properties allow it to chelate and coordinate with metal ions in the host material, forming relatively stable coordination bonds. This results in a strong coupling effect between nitrogen atoms and NFS materials, forming stable Fe-NC bonds. This effectively improves the material's electrical conductivity, prevents Na and Fe mixing, and enhances the stability of the material's internal structure. The formation of Fe-NC bonds and the surface carbon layer can reduce SO42- on the material surface. 2- The resulting electronegativity effectively prevents side reactions between the electrolyte and the electrode surface, improving the material's high-voltage resistance.
[0023] This invention utilizes a high-temperature spray dryer. At room temperature, dimethylimidazole, thiourea dioxide, and urea are difficult to chelate and coordinate with metal ions. High-temperature spray drying instantly forms Fe-N coordination bonds, promoting the formation of nanocrystals and resulting in shorter Na+ crystals. + Migration tunnels promote Na + Effective migration of NFS cathode materials slows down lattice distortion during charging and discharging, further enhancing the resistance of NFS cathode materials to damage during cycling.
[0024] In summary, the high-voltage resistant sodium ferrous sulfate (NFS) cathode material of this invention can effectively improve the energy density of sodium battery cells. This cathode material can increase the charging voltage of sodium battery cells, reduce side reactions between the electrode surface and the electrolyte, and effectively improve the overcharge safety and cycle stability of sodium battery cells under high-voltage conditions. This material provides a key solution for high-voltage sodium batteries, effectively reducing system costs by increasing energy density, and laying an important foundation for the large-scale application of sodium batteries. In addition, the main material of the high-voltage resistant sodium ferrous sulfate (NFS) cathode material is solid waste sodium sulfate (Na2SO4), and the preparation process is simple. The core value of this cathode material lies in giving solid waste sodium sulfate (Na2SO4) a new identity as a key raw material. This application not only directly empowers the improvement of sodium battery performance, but also creates an industrial synergy path of "promoting production through waste and eliminating waste through production", opening up a new situation of win-win economic and environmental benefits. Attached Figure Description
[0025] Figure 1 This is a SEM image of the NFS cathode material. Detailed Implementation
[0026] The following detailed and complete description of the implementation of the technical solution of the present invention, in conjunction with specific embodiments, will facilitate understanding. It should be specifically noted that the listed embodiments are merely some examples and do not exhaustively cover all possible implementations of the present invention. Any other embodiments that can be implemented by those skilled in the art without creative effort based on the technical content disclosed in this invention should be considered to fall within the protection scope of this invention.
[0027] Example 1
[0028] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0029] Step 1: Add 1780g of sodium sulfate, 4865g of ferrous sulfate heptahydrate, 88g of carbon nanotubes, 8L of deionized water, and 2g of citric acid to a mixing tank for dispersion and dissolution. Increase the stirring speed of the impeller to 1000 rpm and add an alcohol solution containing 90g of dimethylimidazole to obtain an NFS precursor slurry containing 2% dimethylimidazole that is uniformly dispersed.
[0030] Step 2: The NFS precursor slurry containing 2% dimethylimidazole was spray-dried using a spray dryer. The inlet air temperature was set to 230℃ and the outlet air temperature was set to 110℃. The high temperature promoted the formation of Fe-N bonds and generated Fe-ZIF derivatives, thus obtaining the NFS cathode material precursor.
[0031] Step 3: Place the prepared NFS cathode material precursor into a graphite crucible, place the graphite crucible into a low-temperature atmosphere furnace, and sinter in a nitrogen atmosphere. Heat the furnace at 2℃ / min to 300℃, 320℃, 340℃, 360℃, and 380℃ and hold for 12 hours to obtain sintered NFS cathode materials, which are labeled as Examples 1.1, 1.2, 1.3, 1.4, and 1.5, respectively.
[0032] Step 4: The sintered cathode material from Examples 1.1-5 is then pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to obtain a high-pressure resistant sodium ferrous sulfate cathode material with uniform particle size distribution.
[0033] Example 2
[0034] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0035] Step 1: Add materials according to the experimental scheme in Example 1, but the amount of dimethylimidazole added is 184g, and an NFS precursor slurry containing 4% dimethylimidazole is obtained with uniform dispersion.
[0036] Step 2: The NFS precursor slurry containing 4% dimethylimidazole is spray-dried using a spray dryer with an inlet air temperature of 230°C and an outlet air temperature of 110°C. The high temperature of the spray dryer drives the reaction to generate an NFS cathode material precursor containing 4% Fe-ZIF derivative.
[0037] Step 3: The prepared NFS cathode material precursor containing 4% Fe-ZIF derivative was placed in a graphite crucible, and the graphite crucible was placed in a low-temperature atmosphere furnace. The sintering atmosphere was nitrogen, and the temperature was increased to 300℃, 320℃, 340℃, 360℃, and 380℃ at a rate of 2℃ / min and held for 12 hours to obtain sintered NFS cathode materials, which were labeled as Examples 2.1, 2.2, 2.3, 2.4, and 2.5, respectively.
[0038] Step 4: Use an air jet mill to pulverize the sintered cathode material from Example 2.1-5 to a particle size of d. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to finally obtain a high-pressure resistant sodium ferrous sulfate cathode material with uniform particle size distribution.
[0039] Example 3:
[0040] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0041] Step 1: Add materials according to the experimental scheme in Example 1. The amount of dimethylimidazole added is 281g. After it is completely dispersed, an NFS precursor slurry containing 6% dimethylimidazole is obtained.
[0042] Step 2: The NFS precursor slurry containing 6% dimethylimidazole is spray-dried using a spray dryer with an inlet air temperature of 230°C and an outlet air temperature of 110°C. The high temperature drives the reaction to generate an NFS cathode material precursor containing 6% Fe-ZIF derivative.
[0043] Step 3: The prepared NFS cathode material precursor containing 6% Fe-ZIF derivative was placed in a graphite crucible, and then the graphite crucible was placed in a low-temperature atmosphere furnace. The sintering atmosphere was nitrogen, and the temperature was increased to 300℃, 320℃, 340℃, 360℃, and 380℃ at a rate of 2℃ / min and held for 12 hours to obtain sintered NFS cathode materials, which were labeled as Examples 3.1, 3.2, 3.3, 3.4, and 3.5, respectively.
[0044] Step 4: The sintered cathode material from Examples 3.1-5 is then pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to finally obtain NFS cathode material with uniform particle size distribution.
[0045] Example 4:
[0046] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0047] Step 1: Add materials according to the experimental scheme in Example 1, wherein the amount of dimethylimidazole added is 383g, and after it is thoroughly dispersed, an NFS precursor slurry containing 8% dimethylimidazole is obtained.
[0048] Step 2: The NFS precursor slurry containing 8% dimethylimidazole is spray-dried using a spray dryer with an inlet air temperature of 230°C and an outlet air temperature of 110°C. The high temperature drives the reaction to generate an NFS cathode material precursor containing 8% Fe-ZIF derivative.
[0049] Step 3: The prepared NFS cathode material precursor containing 8% Fe-ZIF derivative was placed in a graphite crucible, and the graphite crucible was placed in a low-temperature atmosphere furnace. The sintering atmosphere was nitrogen, and the temperature was increased to 300℃, 320℃, 340℃, 360℃, and 380℃ at a rate of 2℃ / min and held for 12 hours to obtain sintered cathode materials, which were labeled as Examples 4.1, 4.2, 4.3, 4.4, and 4.5, respectively.
[0050] Step 4: The sintered cathode material from Examples 4.1-5 is then pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to finally obtain NFS cathode material with uniform particle size distribution.
[0051] Example 5:
[0052] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0053] Step 1: Add materials according to the experimental scheme in Step 1 of Example 1. The amount of dimethylimidazole added is 490g. After it is completely dispersed, an NFS precursor slurry containing 10% dimethylimidazole is obtained.
[0054] Step 2: The NFS precursor slurry containing 10% dimethylimidazole is spray-dried using a spray dryer with an inlet air temperature of 230°C and an outlet air temperature of 110°C. The high temperature drives the reaction to generate an NFS cathode material precursor containing 10% Fe-ZIF derivative.
[0055] Step 3: The prepared NFS cathode material precursor containing 10% Fe-ZIF derivative was placed in a graphite crucible, and then the graphite crucible was placed in a low-temperature atmosphere furnace. The temperature was increased to 300℃, 320℃, 340℃, 360℃, and 380℃ at a rate of 2℃ / min and held for 12 hours to obtain sintered cathode materials, which were labeled as Examples 5.1, 5.2, 5.3, 5.4, and 5.5, respectively.
[0056] Step 4: The sintered cathode material from Examples 5.1-5 is then pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to finally obtain NFS cathode material with uniform particle size distribution.
[0057] Example 6:
[0058] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0059] Step 1: Add 1780g of sodium sulfate, 4865g of ferrous sulfate heptahydrate, 88g of carbon nanotubes, 8L of deionized water, and 2g of citric acid to a mixing tank for dispersion and dissolution. In addition, add 18g of NaOH to the dispersed slurry and stir for 10 minutes to completely dissolve it. Adjust the pH to 10 and increase the stirring speed to 1000 rpm. Add an alcohol solution containing 90g of thiourea dioxide to obtain a uniformly dispersed NFS precursor slurry containing 2% thiourea dioxide.
[0060] Step 2: Use a spray dryer to spray dry the NFS precursor slurry containing 2% thiourea dioxide evenly dispersed. The inlet air temperature is set to 230℃ and the outlet air temperature is set to 110℃. The reaction generates nitrogen-doped NFS cathode material precursor.
[0061] Step 3: The prepared nitrogen-doped NFS cathode material precursor was placed in a graphite crucible, and the graphite crucible was placed in a low-temperature atmosphere furnace. The sintering atmosphere was nitrogen. The temperature was increased to 300℃, 320℃, 340℃, 360℃, and 380℃ at a rate of 2℃ / min and held for 8 hours to obtain sintered NFS cathode materials, which were labeled as Examples 6.1, 6.2, 6.3, 6.4, and 6.5, respectively.
[0062] Step 4: The sintered cathode material from Examples 6.1-5 is then pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to obtain a high-pressure resistant sodium ferrous sulfate cathode material with uniform particle size distribution.
[0063] Example 7:
[0064] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0065] Step 1: The materials were added according to the experimental scheme in Example 6, but the amount of NaOH added was changed to 36.8g and the amount of thiourea dioxide added was changed to 184g, and finally an NFS precursor slurry containing 4% thiourea dioxide was obtained with uniform dispersion.
[0066] Step 2: Prepare nitrogen-doped NFS cathode material precursor according to the experimental scheme in Step 2 of Example 6;
[0067] Step 3: Sinter the cathode materials of Examples 7.1-5 according to the experimental scheme of Step 3 in Example 6;
[0068] Step 4: Following the experimental steps in Step 4 of Example 6, sieve the powder particles that meet the specified particle size d. 50 ≤8um Example 7.1-5 Positive electrode material.
[0069] Example 8:
[0070] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0071] Step 1: The materials were added according to the experimental scheme in Example 6, but the amount of NaOH added was changed to 56.2g and the amount of thiourea dioxide added was changed to 281g, and finally an NFS precursor slurry containing 6% thiourea dioxide was obtained with uniform dispersion.
[0072] Step 2: Prepare nitrogen-doped NFS cathode material precursor according to the experimental scheme in Step 2 of Example 6;
[0073] Step 3: Sinter the cathode materials of Examples 8.1-5 according to the experimental scheme of Step 3 in Example 6;
[0074] Step 4: Following the experimental steps in Step 4 of Example 6, sieve the powder particles that meet the specified particle size d. 50 ≤8um Example 8.1-5 Cathode material.
[0075] Example 9:
[0076] This comparative example illustrates a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, comprising the following steps:
[0077] Step 1: The materials were added according to the experimental scheme in Example 6, but the amount of NaOH added was changed to 76.6g and the amount of thiourea dioxide added was changed to 383g, and finally an NFS precursor slurry containing 8% thiourea dioxide was obtained with uniform dispersion.
[0078] Step 2: Prepare nitrogen-doped NFS cathode material precursor according to the experimental scheme in Step 2 of Example 6;
[0079] Step 3: Sinter Examples 9.1-5 according to the experimental scheme in Step 3 of Example 6;
[0080] Step 4: Following the experimental steps in Step 4 of Example 6, sieve the powder particles that meet the specified particle size d. 50 ≤8µm Example 9.1-5 Cathode material.
[0081] Example 10:
[0082] This comparative example illustrates a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, comprising the following steps:
[0083] Step 1: Add materials according to the experimental scheme in Example 6, but the amount of NaOH added becomes 98g and the amount of thiourea dioxide added becomes 490g, finally obtaining an NFS precursor slurry containing 10% thiourea dioxide evenly dispersed.
[0084] Step 2: Prepare nitrogen-doped NFS cathode material precursor according to the experimental scheme in Step 2 of Example 6;
[0085] Step 3: Sinter Examples 10.1-5 according to the experimental scheme in Step 3 of Example 6;
[0086] Step 4: Following the experimental steps in Step 4 of Example 6, sieve the powder particles that meet the specified particle size d. 50 ≤8um Example 10.1-5 Positive electrode material powder.
[0087] Example 11:
[0088] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0089] Step 1: Add 1780g of sodium sulfate, 4865g of ferrous sulfate heptahydrate, 88g of carbon nanotubes, 8L of deionized water, and 2g of oxalic acid to a mixing tank for dispersion and dissolution. Increase the stirring speed of the agitator to 1000 rpm, add 90g of urea, and stir thoroughly to dissolve, obtaining a uniformly dispersed NFS precursor slurry containing urea.
[0090] Step 2: Use a spray dryer to spray dry the NFS precursor slurry containing 2% urea evenly dispersed. The inlet air temperature is set to 230℃ and the outlet air temperature is set to 110℃ to obtain nitrogen-doped NFS cathode material precursor.
[0091] Step 3: Place the prepared NFS cathode material precursor into a graphite crucible, place the graphite crucible into a low-temperature atmosphere furnace, and sinter in a nitrogen atmosphere. Heat the furnace at 2℃ / min to 300℃, 320℃, 340℃, 360℃, and 380℃ and hold for 12 hours to obtain sintered NFS cathode materials, which are labeled as Examples 11.1, 11.2, 11.3, 11.4, and 11.5, respectively.
[0092] Step 4: The sintered cathode material from Examples 11.1-5 is then pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to obtain a high-pressure resistant sodium ferrous sulfate cathode material with uniform particle size distribution.
[0093] Example 12:
[0094] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0095] Step 1: Add materials according to the experimental scheme in Example 11, but the amount of urea added becomes 184g, and finally a slurry containing 4% urea NFS precursor is obtained.
[0096] Step 2: Prepare a nitrogen-containing NFS cathode material precursor according to the experimental scheme in Step 2 of Example 11;
[0097] Step 3: Sinter the cathode materials of Examples 12.1-5 according to the experimental scheme of Step 3 in Example 11;
[0098] Step 4: Following the experimental steps in Step 4 of Example 11, sieve the powder particles that meet the specified particle size d. 50 ≤8um Example 12.1-5 Positive electrode material.
[0099] Example 13:
[0100] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0101] Step 1: Add materials according to the experimental scheme in Example 11, but the amount of urea added becomes 281g, and finally a slurry containing 6% urea NFS precursor is obtained.
[0102] Step 2: Prepare a nitrogen-containing NFS cathode material precursor according to the experimental scheme in Step 2 of Example 11;
[0103] Step 3: Sinter the cathode materials of Examples 13.1-5 according to the experimental scheme of Step 3 in Example 11;
[0104] Step 4: Following the experimental steps in Step 4 of Example 11, sieve the powder particles that meet the specified particle size d. 50 ≤8um Example 13.1-5 Positive electrode material.
[0105] Example 14:
[0106] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0107] Step 1: Add materials according to the experimental scheme in Example 11, but the amount of urea added becomes 383g, and finally a slurry containing 8% urea NFS precursor is obtained.
[0108] Step 2: Prepare a nitrogen-containing NFS cathode material precursor according to the experimental scheme in Step 2 of Example 11;
[0109] Step 3: Sinter Examples 14.1-5 according to the experimental scheme in Step 3 of Example 11;
[0110] Step 4: Following the experimental steps in Step 4 of Example 11, sieve the powder particles that meet the specified particle size d. 50 ≤8µm Example 14.1-5 Positive electrode material.
[0111] Example 15:
[0112] This embodiment describes a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, including the following steps:
[0113] Step 1: Add materials according to the experimental scheme in Example 11, but the amount of urea added becomes 490g, and finally a slurry containing 10% urea NFS precursor is obtained.
[0114] Step 2: Prepare a nitrogen-containing NFS cathode material precursor according to the experimental scheme in Step 2 of Example 11;
[0115] Step 3: Sinter Examples 15.1-5 according to the experimental scheme in Step 3 of Example 11;
[0116] Step 4: Following the experimental steps in Step 4 of Example 11, sieve the powder particles that meet the specified particle size d. 50 ≤8µm Example 15.1-5 Cathode material.
[0117] Comparative Example 1
[0118] This comparative example illustrates a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, comprising the following steps:
[0119] Step 1: Add 1780g of sodium sulfate, 4865g of ferrous sulfate heptahydrate, 88g of carbon nanotubes, 8L of deionized water, and 2g of citric acid to a mixing tank for dispersion and dissolution. Stir at 800 rpm for 2 hours to thoroughly disperse sodium sulfate, ferrous sulfate heptahydrate, carbon nanotubes, and citric acid in water to obtain a uniformly dispersed NFS precursor slurry.
[0120] Step 2: The dispersed NFS precursor slurry is spray-dried using a spray dryer with an inlet air temperature of 230°C and an outlet air temperature of 110°C to obtain the NFS cathode material precursor.
[0121] Step 3: The prepared NFS cathode material precursor was placed in a graphite crucible, and then the graphite crucible was placed in a low-temperature atmosphere furnace. The temperature was increased to 300℃, 320℃, 340℃, 360℃ and 380℃ at a rate of 2℃ / min and held for 12 hours to obtain cathode materials, which were labeled as comparative examples 1.1, 1.2, 1.3, 1.4 and 1.5, respectively.
[0122] Step 4: Use an air jet mill to pulverize the sintered comparative example 1.1-5 cathode material to a particle size of d. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to finally obtain NFS cathode material powder with uniform particle size distribution.
[0123] Comparative Example 2:
[0124] This comparative example illustrates a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, comprising the following steps:
[0125] Step 1: Add materials according to the experimental scheme in Step 1 of Example 1. The amount of dimethylimidazole added is 45g. After it is completely dispersed, an NFS precursor slurry containing 1% dimethylimidazole is obtained.
[0126] Step 2: The NFS precursor slurry containing 1% dimethylimidazole is spray-dried using a spray dryer with an inlet air temperature of 230°C and an outlet air temperature of 110°C. The high temperature drives the reaction to generate an NFS cathode material precursor containing 10% Fe-ZIF derivative.
[0127] Step 3: The prepared NFS cathode material precursor containing 1% Fe-ZIF derivative was placed in a graphite crucible, and then the graphite crucible was placed in a low-temperature atmosphere furnace. The temperature was increased to 300℃, 320℃, 340℃, 360℃, and 380℃ at a rate of 2℃ / min and held for 12 hours to obtain sintered cathode materials, which were labeled as comparative examples 2.1, 2.2, 2.3, 2.4, and 2.5, respectively.
[0128] Step 4: The sintered comparative example 2.1-5 cathode material is pulverized to a particle size of d using an air jet mill. 50 The particle size is ≤8um, and then sieved through a 300-mesh sieve to finally obtain NFS cathode material with uniform particle size distribution.
[0129] Comparative Example 3:
[0130] This comparative example illustrates a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, comprising the following steps:
[0131] Step 1: Add materials according to the experimental scheme in Example 6, but the amount of NaOH added is changed to 9g and the amount of thiourea dioxide added is changed to 45g, and finally an NFS precursor slurry containing 1% thiourea dioxide is obtained with uniform dispersion.
[0132] Step 2: Prepare nitrogen-doped NFS cathode material precursor according to the experimental scheme in Step 2 of Example 6;
[0133] Step 3: Sinter the cathode material of Comparative Examples 3.1-5 according to the experimental scheme of Step 3 in Example 6;
[0134] Step 4: Following the experimental steps in Step 4 of Example 6, sieve the powder particles that meet the specified particle size d. 50 Comparative Example 3.1-5: Cathode material with a diameter of ≤8µm.
[0135] Comparative Example 4:
[0136] This comparative example illustrates a method for preparing a high-pressure-resistant sodium ferrous sulfate (NFS) cathode material, comprising the following steps:
[0137] Step 1: Add materials according to the experimental scheme in Example 11, but the amount of urea added is 45g, and finally a slurry containing 1% urea NFS precursor is obtained.
[0138] Step 2: Prepare a nitrogen-containing NFS cathode material precursor according to the experimental scheme in Step 2 of Example 11;
[0139] Step 3: Sinter the cathode materials of Comparative Examples 4.1-5 according to the experimental scheme of Step 3 in Example 11;
[0140] Step 4: Following the experimental steps in Step 4 of Example 11, sieve the powder particles that meet the specified particle size d. 50 Comparative Example 4.1-5: Cathode material with a diameter of ≤8µm.
[0141] The sodium ferrous sulfate (NFS) cathode materials of Examples 1-15 and Comparative Examples 1-4 were subjected to coin cell assembly tests. Their charge-discharge performance and cycle performance were tested, and the test results are shown in the table below:
[0142] Table 1:
[0143] 0.1C discharge capacity (mAh / g) 72 82 90 92 89 50-turn capacity retention (2-4.5V) 98% 98% 98.5% 98% 98% sample Example 2.1 Example 2.2 Example 2.3 Example 2.4 Example 2.5 0.1C discharge capacity (mAh / g) 74 84 90 94 89 50-turn capacity retention (2-4.5V) 98% 98% 98.5% 98% 98% sample Example 3.1 Example 3.2 Example 3.3 Example 3.4 Example 3.5 0.1C discharge capacity (mAh / g) 81 86 93 96 94 50-turn capacity retention (2-4.5V) 100% 100.1% 100.2% 100.3% 100.2% sample Example 4.1 Example 4.2 Example 4.3 Example 4.4 Example 4.5 0.1C discharge capacity (mAh / g) 75 82 88 86 82 50-turn capacity retention (2-4.5V) 100% 100% 100% 100% 100% sample Example 5.1 Example 5.2 Example 5.3 Example 5.4 Example 5.5 0.1C discharge capacity (mAh / g) 73 82 86 88 85 50-turn capacity retention (2-4.5V) 99% 99% 99% 99% 99%
[0144] Table 2:
[0145] 0.1C discharge capacity (mAh / g) 81 86 92 95 91 50-turn capacity retention (2-4.5V) 100% 100.12% 100.1% 100.1% 100.1% sample Example 7.1 Example 7.2 Example 7.3 Example 7.4 Example 7.5 0.1C discharge capacity (mAh / g) 77 78 85 90 88 50-turn capacity retention (2-4.5V) 100% 100.12% 100.1% 100.1% 100.1% sample Example 8.1 Example 8.2 Example 8.3 Example 8.4 Example 8.5 0.1C discharge capacity (mAh / g) 72 75 80 85 86 50-turn capacity retention (2-4.5V) 99% 99% 99% 99% 99% sample Example 9.1 Example 9.2 Example 9.3 Example 9.4 Example 9.5 0.1C discharge capacity (mAh / g) 75 76 81 87 82 50-turn capacity retention (2-4.5V) 100% 100% 100% 100% 100% sample Example 10.1 Example 10.2 Example 10.3 Example 10.4 Example 10.5 0.1C discharge capacity (mAh / g) 73 75 78 83 78 50-turn capacity retention (2-4.5V) 100% 100% 100% 100% 100%
[0146] Table 3:
[0147] 0.1C discharge capacity (mAh / g) 78 80 84 88 85 50-turn capacity retention (2-4.5V) 99% 99% 99% 99% 99% sample Example 12.1 Example 12.2 Example 12.3 Example 12.4 Example 12.5 0.1C discharge capacity (mAh / g) 84 88 90 93 90 50-turn capacity retention (2-4.5V) 100% 100% 100% 100% 100% sample Example 13.1 Example 13.2 Example 13.3 Example 13.4 Example 13.5 0.1C discharge capacity (mAh / g) 80 85 87 90 88 50-turn capacity retention (2-4.5V) 99% 99% 99% 99% 99% sample Example 14.1 Example 14.2 Example 14.3 Example 14.4 Example 14.5 0.1C discharge capacity (mAh / g) 77 80 85 90 88 50-turn capacity retention (2-4.5V) 100% 100% 100% 100% 100% sample Example 15.1 Example 15.2 Example 15.3 Example 15.4 Example 15.5 0.1C discharge capacity (mAh / g) 75 80 85 90 88 50-turn capacity retention (2-4.5V) 100% 100% 100% 100% 100%
[0148] Table 4:
[0149] 0.1C discharge capacity (mAh / g) 60 62 67 70 72 50-turn capacity retention (2-4.5V) 91% 92% 93.5% 94% 94% sample Comparative Example 2.1 Comparative Example 2.2 Comparative Example 2.3 Comparative Example 2.4 Comparative Example 2.5 0.1C discharge capacity (mAh / g) 68 74 76 80 80 50-turn capacity retention (2-4.5V) 95% 96.5% 97% 97.5% 97% sample Comparative Example 3.1 Comparative Example 3.2 Comparative Example 3.3 Comparative Example 3.4 Comparative Example 3.5 0.1C discharge capacity (mAh / g) 68 70 72 75 75 50-turn capacity retention (2-4.5V) 95% 96% 96.5% 97% 96% sample Comparative Example 4.1 Comparative Example 4.2 Comparative Example 4.3 Comparative Example 4.4 Comparative Example 4.5 0.1C discharge capacity (mAh / g) 65 67 72 75 75 50-turn capacity retention (2-4.5V) 94% 95% 96% 96% 94%
[0150] Referring to the data in the table above, it can be seen that the high-pressure resistant sodium ferrous sulfate (NFS) cathode material of the present invention has high discharge performance and high stability under high pressure.
[0151] According to the examples and comparative examples, the discharge capacity is the highest at a sintering temperature of 360°C, showing good electrochemical performance. As can be seen from Comparative Examples 1-4, the electrical performance of the products containing dimethylimidazole, thiourea dioxide, and urea is better.
[0152] Comparison of the examples shows that 6% dimethylimidazole, 2% thiourea dioxide, and 4% urea exhibit the best performance, demonstrating high discharge capacity and long cycle performance. The results indicate that adding nitrogen-containing small molecules during the synthesis of NFS cathode materials can participate in the material synthesis reaction, and the presence of nitrogen can interact with Fe... 2+ The formation of Fe-N bond chains effectively improves the conductivity of the material and generates a uniform artificial CEI film. The formation of a uniform CEI film can effectively prevent direct contact between the electrode surface and the electrolyte, thereby preventing the electrolyte from decomposing at high potentials.
[0153] Furthermore, SEM images show that the addition of dimethylimidazole promotes the formation of primary nanoparticles, indicating that dimethylimidazole reacts with Fe... 2+ A chelation reaction occurred, producing a metal-organic framework compound. This compound can construct an artificial CEI film on the electrode surface, thus enabling the prepared NFS cathode material to exhibit optimal electrochemical performance. However, with increasing nitrogen content, the performance significantly decreased, indicating that excessive nitrogen doping occupies more activation sites in the NFS cathode material, thereby inhibiting its activity.
[0154] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0155] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-pressure-resistant sodium ferrous sulfate cathode material, characterized in that, The preparation method includes the following steps: Step 1: Add sodium sulfate, ferrous sulfate, carbon nanotubes, deionized water and dispersant to a mixing tank for dispersion and dissolution, and then add an alcohol solution containing nitrogen small molecules to obtain NFS precursor slurry. Step 2: Use a spray dryer to spray dry the mixed slurry to obtain the NFS cathode material precursor; Step 3: Place the prepared NFS cathode material precursor into a graphite crucible, place the graphite crucible into a low-temperature atmosphere furnace, and sinter to obtain the sintered NFS cathode material. Step 4: The prepared NFS cathode material is pulverized using an air jet mill and then sieved through a 300-mesh sieve to obtain a high-pressure-resistant sodium ferrous sulfate cathode material with uniform particle size distribution.
2. The method for preparing the high-pressure-resistant sodium ferrous sulfate cathode material according to claim 1, characterized in that, In step one, the molar ratio of sodium sulfate to ferrous sulfate is 1.25:1.75; the mass of carbon nanotubes is 1-5% of the total solid mass.
3. The method for preparing the high-pressure-resistant sodium ferrous sulfate cathode material according to claim 1, characterized in that, In step one, the nitrogen-containing small molecule is one or more of dimethylimidazole, thiourea dioxide, and urea, and its mass is 2-10% of the total solid mass. Among them, thiourea dioxide contains sulfur, and to ensure variable stability, a small amount of sodium source needs to be added when using thiourea dioxide.
4. The method for preparing the high-pressure-resistant sodium ferrous sulfate cathode material according to claim 1, characterized in that, In step one, the dispersant is one of citric acid, glucose, oxalic acid, polyethylene glycol, polyethylene oxide, and ammonium polyacrylate.
5. The method for preparing the high-pressure-resistant sodium ferrous sulfate cathode material according to claim 1, characterized in that, In step two, when performing spray drying, the inlet air temperature is set to 230°C and the outlet air temperature is set to 110°C.
6. The method for preparing the high-pressure-resistant sodium ferrous sulfate cathode material according to claim 1, characterized in that, In step three, the sintering atmosphere is nitrogen, the sintering temperature is 300-380℃, the heating rate is 2℃ / min, and the sintering holding time is 8-12h.
7. The method for preparing the high-pressure-resistant sodium ferrous sulfate cathode material according to claim 1, characterized in that, In step four, when using an air jet mill for pulverization, the particle size is pulverized to d. 50 ≤8um.
8. A high-pressure-resistant sodium ferrous sulfate cathode material, characterized in that, The cathode material is prepared by the method described in any one of claims 1-7.
